2013
DOI: 10.1111/j.1728-4465.2013.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

The Need to Reemphasize Behavior Change for HIV Prevention in Uganda: A Qualitative Study

Abstract: The need to reemphasize behavior change for hiv prevention in Uganda: A qualitative study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In addition to the concerns that have been raised about the content of Uganda's HIV prevention strategies directed at young people, critics have recently pointed out that Uganda's funding and policy strategies disproportionately focus on AIDS treatment rather than on behavioural strategies for reducing HIV transmission (Green et al 2013;UAC 2015).…”
Section: Sexuality Education Programmes In Ugandamentioning
confidence: 99%
“…In addition to the concerns that have been raised about the content of Uganda's HIV prevention strategies directed at young people, critics have recently pointed out that Uganda's funding and policy strategies disproportionately focus on AIDS treatment rather than on behavioural strategies for reducing HIV transmission (Green et al 2013;UAC 2015).…”
Section: Sexuality Education Programmes In Ugandamentioning
confidence: 99%
“…Abstinence and messages related to being faithful to their partners should also be emphasized for men. Other research suggests that recent HIV prevention efforts in Uganda have de-emphasize partner reduction strategies [15,16]. We found that the partner reduction message was common, but was being used asymmetrically.…”
Section: Resultsmentioning
confidence: 67%
“…These recent increases in HIV prevalence have reinvigorated an interest in the HIV prevention messages and programs that are currently being implemented, and how they are being understood by community members. In particular, there is concern about behavioral disinhibition because HIV messages in country may now emphasize HIV testing and treatment, rather than sexual behavior change strategies [15,16]. This study aimed to elucidate and examine gendered and generational perspectives on HIV prevention messages in Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the study community reported that they mainly heard HIV prevention messages centered on condoms and testing, a marked shift from the partner reduction messages common during the years in which HIV incidence was declining in Uganda (16). In focus groups, members of the study community reported that people no longer feared HIV as they had during the epidemic’s peak and that this had led to riskier sexual behavior (17).…”
Section: Introductionmentioning
confidence: 99%